Long noncoding RNA dysregulation in ischemic heart failure. Issue 1 (December 2016) - Greco, Simona; Zaccagnini, Germana; Perfetti, Alessandra; Fuschi, Paola; Valaperta, Rea; Voellenkle, Christine; Castelvecchio, Serenella; Gaetano, Carlo; Finato, Nicoletta; Beltrami, Antonio; Menicanti, Lorenzo; Martelli, Fabio
Abstract Background Long noncoding RNAs (lncRNAs) are non-protein coding transcripts regulating a variety of physiological and pathological functions. However, their implication in heart failure is still largely unknown. The aim of this study is to identify and characterize lncRNAs deregulated in patients affected by ischemic heart failure. Methods LncRNAs were profiled and validated in left ventricle biopsies of 18 patients affected by non end-stage dilated ischemic cardiomyopathy and 17 matched controls. Further validations were performed in left ventricle samples derived from explanted hearts of end-stage heart failure patients and in a mouse model of cardiac hypertrophy, obtained by transverse aortic constriction. Peripheral blood mononuclear cells of heart failure patients were also analyzed. LncRNA distribution in the heart was assessed by in situ hybridization. Function of the deregulated lncRNA was explored analyzing the expression of the neighbor mRNAs and by gene ontology analysis of the correlating coding transcripts. Results Fourteen lncRNAs were significantly modulated in non end-stage heart failure patients, identifying a heart failure lncRNA signature. Nine of these lncRNAs (CDKN2B-AS1/ANRIL, EGOT, H19, HOTAIR, LOC285194/TUSC7, RMRP, RNY5, SOX2-OT and SRA1) were also confirmed in end-stage failing hearts. Intriguingly, among the conserved lncRNAs, h19, rmrp andhotair were also induced in a mouse model of heart hypertrophy. CDKN2B-AS1/ANRIL, HOTAIR and LOC285194/TUSC7 showed similar modulation in peripheral blood mononuclear cells and heart tissue, suggesting a potential role as disease biomarkers. Interestingly, RMRP displayed a ubiquitous nuclear distribution, while H19 RNA was more abundant in blood vessels and was both cytoplasmic and nuclear. Gene ontology analysis of the mRNAs displaying a significant correlation in expression with heart failure lncRNAs identified numerous pathways and functions involved in heart failure progression. Conclusions These data strongly suggest lncRNA implication in the molecular mechanisms underpinning HF.